Penerapan Rekayasa Nilai (Value Engineering) pada Bangunan Rumah Susun Sederhana (Studi Kasus: Rusunawa Jongke Sleman) - Natalie, Jap Yovita; Kaming, Peter F.; Koesmargono, A. (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2020)
The construction of apartment units which is certain to increase every year, of course must be followed by the construction and management of good and planned. In previous studies with the title